Lingual Abscess in a Psychiatric Patient: A Case Report - D. Kikidis; K. Marinakis; J. Sengas; A. Chrysovergis (Case Reports in Medicine)
We present a 46-year-old psychiatric patient presenting with a lingual abscess. This paper covers the epidemiology, clinical features, diagnosis, and differential diagnosis with a view to assisting emergency physicians in the timely recognition and management of this rare but potentially life-threatening condition.